Measuring and optimising patient-reported outcomes in eczema clinical trials through the use of online methods - Baker, Arabella (2024)
Background Eczema is a chronic, inflammatory, itchy skin condition affecting 15-30% children and 2-10% adults. In randomised controlled trials (RCTs), patient-reported outcome measures (PROMs) are often used to evaluate interventions. The Harmonising Outcome Measures for Eczema (HOME) initiative developed a core outcome set (COS) consisting of four core domains to be included in all eczema trials, three of which are measured with PROMs. Implementing the COS helps to improve the consistency of outcome measures and the comparability of results across eczema trials. However, the optimum frequency of PROM assessments in eczema trials is unclear, which may hinder the uptake of the full COS.